The THO/TREX Complex Component RAE2/TEX1 Is Involved in the Regulation of Aluminum Resistance and Low Phosphate Response in Arabidopsis - Zhu, Yi-Fang; Guo, Jinliang; Zhang, Yang; Huang, Chao-Feng (Frontiers in Plant Science, 2021)
The C2H2-type zinc finger transcription factor SENSITIVE TO PROTON RHIZOTOXICITY 1 (STOP1) plays a critical role in aluminum (Al) resistance and low phosphate (Pi) response mainly through promoting the expression of the malate transporter-encoding gene ARABIDOPSIS THALIANA ALUMINUM ACTIVATED MALATE TRANSPORTER 1 (AtALMT1). We previously showed that REGULATION OF ATALMT1 EXPRESSION 3 (RAE3/HPR1), a core component of the THO/TREX complex, is involved in the regulation of nucleocytoplasmic STOP1 mRNA export to modulate Al resistance and low Pi response. Here, we report that RAE2/TEX1, another core component of the THO complex, is also involved in the regulation of Al resistance and low Pi response. Mutation of RAE2 reduced the expression of STOP1-downstream genes, including AtALMT1. rae2 was less sensitive to Al than rae3, which was consistent with less amount of malate secreted from rae3 roots than from rae2 roots. Nevertheless, low Pi response was impaired more in rae2 than in rae3, suggesting that RAE2 also regulates AtALMT1-independent pathway to modulate low Pi response. Furthermore, unlike RAE3 that regulates STOP1 mRNA export, mutating RAE2 did not affect STOP1 mRNA accumulation in the nucleus, although STOP1 protein level was reduced in rae2. Introduction of rae1 mutation into rae2 mutant background could partially recover the deficient phenotypes of rae2. Together, our results demonstrate that RAE2 and RAE3 play overlapping but distinct roles in the modulation of Al resistance and low Pi response.